2021
DOI: 10.3389/fmed.2021.644376
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Signatures of Autoimmune Hepatitis in the Development of Cirrhosis

Abstract: Objectives: Autoimmune hepatitis (AIH) can progress into severe outcomes, i.e., decompensated cirrhosis, from remarkable and persistent inflammation in the liver. Considering the energy-expending nature of inflammation, we tried to define the metabolomics signatures of AIH to uncover the underlying mechanisms of cirrhosis development and its metabolic biomarkers.Methods: Untargeted metabolomics analysis was performed on sera samples from 79 AIH patients at the stages (phenotypes) of non-cirrhosis (n = 27), com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
(35 reference statements)
1
10
0
Order By: Relevance
“…Our results demonstrated that trans- 2-enoyl-OPC4-CoA was downregulated during ascites production and progress. Interestingly, trans- 2-enoyl-OPC4-CoA was also found to be significantly reduced in autoimmune hepatitis-related cirrhosis (AIH) as shown in our previous study ( 15 ). The similar liver response triggered by AIH compared with alcohol consumption suggests that trans- 2-enoyl-OPC4-CoA downregulation might be a common characteristic of cirrhosis progress.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our results demonstrated that trans- 2-enoyl-OPC4-CoA was downregulated during ascites production and progress. Interestingly, trans- 2-enoyl-OPC4-CoA was also found to be significantly reduced in autoimmune hepatitis-related cirrhosis (AIH) as shown in our previous study ( 15 ). The similar liver response triggered by AIH compared with alcohol consumption suggests that trans- 2-enoyl-OPC4-CoA downregulation might be a common characteristic of cirrhosis progress.…”
Section: Discussionsupporting
confidence: 76%
“…Data processing and statistical analysis were carried out based on those by Huang et al ( 13 15 ). Briefly, metabolomic data were normalized by the inclusion of multiple internal standards and pool calibration–response correction in MetaboAnalyst version 4.0 after being processed in MassHunter Profinder 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The immune system competes with other programs in the body for energy. In addition, the energy supply is significantly disordered in the body, which is mainly manifested in the large consumption of nutrients (such as carbohydrate, proteins and lipids) and the enhancement of degradation in carbohydrate, lipid and protein ( Freitas et al., 2018 ; Li et al., 2021 ). In our study, the gene function which was significant enriched in AIH were mainly associated with energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It improves mitochondrial functions and exerts beneficial effects in neurological disorders ( 49 ). An upregulated lysoPA correlated with the occurrence of several inflammatory conditions, such as asthma ( 50 ), cancer ( 51 ), and autoimmune hepatitis ( 52 ). We identified phosphatidylserine (PS), phosphatidylethanolamine (PE), and lysoPA as differential serum metabolites in NMDAR encephalitis patients versus controls.…”
Section: Discussionmentioning
confidence: 99%